Teaching Using Comis As A Media To Improve Student’s Vocabulary Mastery At Tenth Grade of SMAN 1 Muntok - Suwastomo, Bambang (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2016)
The main purposes of this thesis is to know the implementation of Comic as a Media in improving student‟s vocabulary mastery and to know whether any significant difference or not in improving vocabulary mastery of the students who were taught by using Comic as a Media. In this thesis the researcher uses quantitative approach with quasi-experimental design. The population of the study is all of the tenth grade students of SMAN 1 MUNTOK that consists of 212 students, while the samples of the research are 55 students. The result of the test is analyzed by using statistical analysis of Paired sample t-test and Independent sample t-test. The researcher uses Coefficient Correlation and Cronbach Alpha to know the validity and reliability of the test. There are two research findings in this research. First, there are a significant difference in vocabulary achievement before and after using Comic as a Media. From the result of the paired sample t-test, it is proved that the mean of post-test experimental group (73.81), is higher than pre-test (61.43). The result of t-obtained is 4.11 higher than 2.02 of the critical value of t-table (at the significant level 0.05 in two tailed testing degree of freedom 22). In addition, there is a significant difference experimental group and control group. It shows that from the difference analysis on post-test of experimental and control group. It can be seen from the result of the independent samples t-test. It is found that p-output was 0.000 for sig. (2-tailed). Since the p-output value was lower than 0.05. Thus, the null hypothesis (Ho) is rejected and the research hypothesis (Ha) is accepted. In other words, there is a significant difference in reading achievement between students‟ who is taught by Comic as a Media and those who are not. Therefore, Comic as a Media is one strategy that can influence students‟ vocabulary achievement.